Differential expression of poliovirus receptor, regulator of G-protein signaling 11 and erythrocyte protein band 4.1-like 3 in human granulosa cells during follicular growth and maturation. (September 2014) - Barzilay, Eran; Yung, Yuval; Shapira, Lev; Haas, Jigal; Ophir, Libby; Yerushalmi, Gil M.; Maman, Ettie; Hourvitz, Ariel
Abstract Poliovirus receptor (PVR), regulator of G-protein signaling-11 (RGS11), and erythrocyte protein band-4.1-like 3 (EPB41L3) have been proposed to function in follicular maturation in mouse models. We have examined their expression in human mural (mGCs) and cumulus granulosa cells (CCs). Expression of PVR and RGS11 in mGCs decreased in medium-sized follicles compared to small follicles of IVM cycles and increased again in large follicles. Luteinization caused decreased expression of both PVR and RGS11. In vitro incubation of mGCs with progesterone-rich conditioned media decreased expression of RGS11 without affecting PVR levels. Inhibition of progesterone signaling enhanced expression of both RGS11 and PVR. Expression in CCs was examined by means of global transcriptome sequencing analysis RGS11 and EPB41L3 increased in CCs during follicular maturation while PVR levels did not change. In conclusion, during human follicular maturation there are significant changes in expression of PVR, RGS11 and EPB41L3, possibly regulated by progesterone.